A critical study of the evaluation of foetal maturity through citology of the amniotic fluid: comparison with other methods - Almeida, Pedro Augusto Marcondes de; Oliveira, Ana Maria Bertini de; Porto, Antonio Guilherme Moreira; Delascio, Domingos; Vigorito, Neusa Maria; Chow, Prescilla; Amed, Abes Mohamed; Dalla, Ari; Boyacyan, Krikor; Baugartner, Adelheid (Revista de Saúde Pública, 1975)
Through amniocentesis carried ou in 90 high-risk pregnant women a critical study of the citology of the amniotic fluid by the Nile-blue sulphate method was undertaken. The results were compared with those obtained by using creatinine and simple X-rays of the abdomen as well as their relationship with the foetal-age of the babies when born (calculated by the Lubchenco and Capurro tables). The Nile-blue sulphate method is of considerable value due to conditions in Brazil and presents a lower percentage of errors than others. For evaluation of foetal maturity, however, one should use all methods simultaneously, along with clinical assessment.